Physical Design Analysis Learning Videos Titled “What Is That Form?” - Rani Nuraeni; Seni Apriliya; Resa Respati (Indonesian Journal of Primary Education, 2021)
The purpose of this study is to describe the physical design of elementary school form learning videos in the Ruangguru application. This study uses a qualitative approach with content analysis methods. The source of data in this study is a video learning Indonesian class VI, the form material in the Ruangguru application entitled “Formulir Itu Apa Ya” is supported by the results of interviews with the narrator in the learning video. The results show that there is accessibility, visibility and timing. The accessibility of this learning video in the ease of accessing the video is classified as good access because the stages in accessing the video are easy to understand by the user, the exposure of the information displayed helps the user to access it as desired. Visibility regarding the clarity of audio, images and text in the learning video is quite clear because the audio is always clear, display in the form of animated images made with digital engineering technology with a resolution on this video that can be selected according to the user's wishes, namely 480p / 234 kbps or 720p / 351 kbps, and the text in this learning video is both the size, type and color of the writing in the proportional program. The timing of the tempo setting in the introduction, content, and closing of this learning video is quite efficient. The tempo setting in the introduction is 44 seconds, the tempo setting on the content is or 6 minutes 34 seconds, and the closing tempo setting is 10 seconds. Judging from the physical design, the learning video entitled “Formula Itu Apa Ya” is recommended to be used by teachers for teaching because it meets good video standards.